Efisiensi Alokasi Sumber Daya Sektor Kesehatan di Provinsi Jawa Barat Tahun 2023 - Fernando, Billy; Hakim, Arif Rachman; Indahwati, Indahwati (Jurnal Ekonomika : INDEPENDEN, 2025)
This empirical study aims to measure the level of technical efficiency in resource allocation within the health sector, including Health Expenditure, Health Personnel, and Hospitals, in converting this investment into human development outcomes, namely Life Expectancy (AHH) and the Human Development Index (IPM), across 27 Districts/Cities in West Java in 2023. The research evaluates fiscal decentralization policies and validates the Human Capital Theory. The methodology employed a quantitative, analytical descriptive approach, utilizing the non-parametric Data Envelopment Analysis (DEA), specifically the Input Oriented CRS Model, with all 27 Districts/Cities designated as Decision Making Units (DMU). DEA results indicate that the majority of DMUs in West Java operate at an inefficient level (theta < 1). Only Tasikmalaya and Pangandaran Districts were declared absolutely efficient, while Subang District, Tasikmalaya City, and Cimahi City were identified as the most technically inefficient units. Slack Analysis provided tangible evidence that the primary source of inefficiency is rooted in significant input overuse (Islack), especially in Health Expenditure. In conclusion, the technical inefficiency in West Java is a persistent and structural resource management problem, necessitating a necessary shift in managerial focus from absolute input fulfillment toward optimizing input conversion.